Peran Komunikasi Keluarga Dalam Membangun Motivasi Pada Anak Pengidap Kanker - Nurfamila, Aisya Rahma Putri; Aprianti, Agus (eProceedings of Management, 2024)
Family communication between parents and children with cancer is quite different when compared to communicationthat occurs between parents and children who do not have cancer in general, because the presence of cancer inchildren not only brings physical pain, but also brings deep emotional trauma. The purpose of this research is to findout how the role of family communication in building motivation in children with cancer. The main theory of thisresearch uses Family Communication Patterns Theory from Koerner and Fitzpatrick 2002. The method in thisresearch is qualitative by collecting primary data through interviews, observation, and documentation. The keyinformants in this research are parents who have children with cancer. The research location took place at AmbuCancer Fighters House, which is located at Jalan Bijaksana Dalam Number 11, Bandung City, West Java. The resultsshowed that open, supportive, intensive and unrestricted family communication, as well as the application of abalanced conformation orientation played an important role in building the motivation of children with cancer. Thetypes of family communication encountered, namely consensual, pluralistic, and protective, can provide a supportiveenvironment to develop positive motivation for children with cancer, where children can remain energized,empowered and optimistic during their recovery period. Keywords-family communication, children with cancer, motivation.